INVESTIGATION THE EFFECT OF THE PERCENT COMPOSITION OF EXHAUST GASES FROM A COMBUSTION CHAMBER OF A THREEBED REGENERATIVE THERMAL OXIDIZER IN THE HEAT RADIATION EXCHANGE DEVELOPED DURING COMBUSTION, THAT NEUTRALIZES GASEOUS POLLUTANTS FOR A GIVEN PLANT CA - Pittas, Nicholas; Margaris, Dionissios; Georgiou, Demos; Grapsa, Theodoula (International Journal of Engineering Technologies and Management Research, 2018)
The purpose of this paper is to study the influence of the composition of the flue gases on the thermal radiation inside the combustion chamber of a three-stage regenerative oxidizer that neutralizes gaseous pollutants for a given plant capacity. This composition is expressed by the corresponding partial pressure of each constituent gas. It is assumed that the flue gases are gray and obey Lambert’s law, so that the gas mixture is assumed to be composed of water vapor and carbon dioxide plus a neutral one. Accurate estimates of each gaseous component emissivity were calculated from the experimental data charts provided by H. Hottel by employing regression analysis. The total emissivity coefficients of the gaseous mixture are evaluated with the help of the above emissivities and they are incorporated into the energy conservation equation that relates the heat exchange among the chamber walls.